2018
DOI: 10.21769/bioprotoc.2675
|View full text |Cite
|
Sign up to set email alerts
|

Mutant Huntingtin Secretion in Neuro2A Cells and Rat Primary Cortical Neurons

Abstract: Quantitative analysis of proteins secreted from the cells poses a challenge due to their low abundance and the interfering presence of a large amount of bovine serum albumin (BSA) in the cell culture media. We established assays for detection of mutant huntingtin (mHtt) secreted from Neuro2A cell line stably expressing mHtt and rat primary cortical neurons by Western blotting. Our protocol is based on reducing the amounts of BSA in the media while maintaining cell viability and secretory potential, and concent… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

1
4
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(5 citation statements)
references
References 5 publications
1
4
0
Order By: Relevance
“…However, to our knowledge, we are the first to identify that this effect is a particular issue in primary neuronal cultures. These findings are also in line with data showing high amounts of BSA in B27-supplemented culture medium which can interfere with subsequent target protein analysis (Trajkovic et al, 2018). This phenomenon may be a particular issue for primary neuronal culture, where cells are maintained for extended periods to allow development of a relatively mature neuronal phenotype, necessitating numerous replenishments of fresh medium.…”
Section: Discussionsupporting
confidence: 84%
“…However, to our knowledge, we are the first to identify that this effect is a particular issue in primary neuronal cultures. These findings are also in line with data showing high amounts of BSA in B27-supplemented culture medium which can interfere with subsequent target protein analysis (Trajkovic et al, 2018). This phenomenon may be a particular issue for primary neuronal culture, where cells are maintained for extended periods to allow development of a relatively mature neuronal phenotype, necessitating numerous replenishments of fresh medium.…”
Section: Discussionsupporting
confidence: 84%
“…2eeg, Supplementary Video 2). Studies on mHTT secretion mechanisms have revealed that mHTT proteins can exit cells via an unconventional late endosomal and lysosomal secretory pathway in a free, non-vesicular form [19,20], or through an exosome or microvesiclemediated transport in an extracellular vesicle-enclosed form [10,21]. The two types of granules likely represent transmissive mHTT released through different mechanisms.…”
Section: Clem and Cryo-et Resolved The 3d Architecture Of Two Types O...mentioning
confidence: 99%
“…Images of blots were captured on a ChemiDoc Touch Imaging System and band intensities of proteins of interest relative to reference protein bands were determined using Image Lab software (both from Bio Rad). We and other groups have previously used ubiquitously expressed secreted and structural proteins as references for equal loading across CM samples in WB ( 57 , 60 , 61 ). To determine a suitable reference protein for the bovine MDEC CM samples in this study, CM from 3 bovine MDEC lines were run on a WB, each as undiluted, diluted 1:2, and diluted 1:4.…”
Section: Methodsmentioning
confidence: 99%